Perspectivas de formação integrada nos cursos técnicos do IFMT – Campus Rondonópolis - Wesz, Rudinei Itamar Tamiosso (2018)
This study had as main objective to identify and analyze the perspectives of integrated training in the technical courses of the Federal Institute of Education, Science and Technology of Mato Grosso (IFMT) / Rondonópolis Campus. We chose three courses as objects of analysis of this research, being: Integrated Food Technician at the Middle Level, Integrated Chemistry Technician at the Medium Level and the Technical Course at Integrated Middle Level Secretariat. The research comprises a qualitative bibliographical and documentary approach. The method adopted is historical-dialectical materialism, based on Marx's thought, which theoretically makes it possible to understand the educational reality, since the Marxist dialectic is opposed to the formal logic that has become insufficient to understand this process. The study points to the importance of professional education based on the conception of human emancipatory omnilateral training and work as an educational principle. The results show that there are ambiguities and contradictions in the three courses analyzed, regarding the concept of integrated vocational training a conception of training demanded by the labor market and another polytechnic, aiming at integral human formation. Professional education, according to the principles of the unitary and polytechnical school, enables the emancipatory formation, through which the subjects are able to understand the social, economic, political and cultural reality, being able to contribute and act in accordance with the collective interests, aiming at a society.